Architectonics of the Augmented City. Distension, extension, tuning - Roig, Eduardo (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2014)
The emergence of the augmented environment, where the digital layer overlaps the physical environment, procures deep changes in the city and in its inhabitants. The insertion of this digital dimension varies the dichotomous boundaries in which the urban structure has been traditionally segregated. The user tunes the Augmented City fitting the topological structure of the new electronic extension. This process of reality symbiosis produces new landscapes, whose architectonic cartography demands a new language to name and to categorize those concepts generated by the Augmented City.